Eaton’s reagent catalysed alacritous synthesis of 3-benzazepinones - Thimmaiah, Shubhavathi; Ningegowda, Mallesha; Shivananju, Nanjunda Swamy; Ningegowda, Raghu; Siddaraj, Ranjith; Priya, Babu Shubha (European Journal of Chemistry, 2016)
An expeditious method for the synthesis of 3-benzazepinones has been developed by using a mixture of phosphorus pentoxide-methane sulfonic acid (Eaton’s reagent) at room temperature under solvent and metal catalyst free condition. Wide functional group tolerance, mild reaction conditions, simple procedure, ease of work-up and high yields is the citable features of this protocol.